A pure and stable intermediate phase is key to growing aligned and vertically monolithic perovskite crystals for efficient PIN planar perovskite solar cells with high processibility and stability. (April 2017) - Bai, Yang; Xiao, Shuang; Hu, Chen; Zhang, Teng; Meng, Xiangyue; Li, Qiang; Yang, Yinglong; Wong, Kam Sing; Chen, Haining; Yang, Shihe
Abstract: Solvent engineering has been extensively used to control the growth of a high-quality perovskite layer for solar cells by forming intermediate phases. However, the intermediate phase formation is often poorly understood and its effects on the perovskite layer growth are still elusive. Here, we have conducted a systematic and in-depth study on the above two issues through a strict control over the DMSO/DMF ratio in CH3 NH3 PbI3 perovskite solutions, and thus an effective control over the compositions of intermediate films. The films thus obtained, including perovskite, perovskite/MA2 Pb3 I8 (DMSO)2 and MA2 Pb3 I8 (DMSO)2, afford perovskite crystals via down-growth, down-and up-growth, and up-growth mechanisms, respectively. Significantly, the up-growth perovskite crystals from the pure MA2 Pb3 I8 (DMSO)2 exhibits the best interface contact with NiO substrate, optimal alignment without horizontal grain boundaries and a relatively large grain size, which facilitate charge transfer and reduce charge recombination in PSCs. As a result, the PIN planar PSCs based on NiO have achieved a PCE of 18.4%, a value which is among the highest for NiO-based PSCs, with the highest stability among the tested sample cells. Furthermore, the pure MA2 Pb3 I8 (DMSO)2 intermediate phase presents a high long-term stability, which enlarges the operating window for perovskite deposition and thus considerably improves the device processibility. Graphical abstract: A pure and stable intermediate phase can drastically facilitate the growth of a perovskite layer with aligned and vertically monolithic crystals on a NiO nanocrystal film, leading to a high PCE of ~18.4% also with significantly improved cell stability and processibility. Highlights: Growth of aligned and vertical monolithic perovskite crystal film via a pure intermediate phase. The monolithic perovskite crystal film facilitates charge transfer and suppresses charge recombination process. A power conversion efficiency of 18.4% is obtained on the NiO-based planar PSCs. Pure intermediate phase leads to outstanding reproducibility and processibility on planar device.